2019
DOI: 10.3390/e21030270
|View full text |Cite
|
Sign up to set email alerts
|

Entropic Uncertainty Relations via Direct-Sum Majorization Relation for Generalized Measurements

Abstract: We derive an entropic uncertainty relation for generalized positive-operator-valued measure (POVM) measurements via a direct-sum majorization relation using Schur concavity of entropic quantities in a finite-dimensional Hilbert space. Our approach provides a significant improvement of the uncertainty bound compared with previous majorization-based approaches [S. Friendland, V. Gheorghiu and G. Gour, Phys. Rev. Lett. 111, 230401 (2013); A. E. Rastegin and K.Życzkowski, J. Phys. A, 49, 355301 (2016)], particular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Entropic PURs in quantum theory can be derived also by means of majorization [122,123,124,125,126,127]. This method of majorization can be also applied to GPTs.…”
Section: Remark 39mentioning
confidence: 99%
“…Entropic PURs in quantum theory can be derived also by means of majorization [122,123,124,125,126,127]. This method of majorization can be also applied to GPTs.…”
Section: Remark 39mentioning
confidence: 99%
“…Remark 3.1.1. Entropic PURs in quantum theory can be derived also by means of majorization [51][52][53][54][55][56]. This method of majorization can be also applied to GPTs.…”
Section: Entropic Pursmentioning
confidence: 99%
“…In this sense, we say that the Rényi entropy is deemed as a generalization of Shannon entropy. Based on Rényi entropy, for generalized positive‐operator‐valued measure (POVM) measurements, the uncertainty relation is derived by utilizing a direct‐sum majorization relation . In addition, Maassen and Uffink have shown that Equation could be generalzied to more general case by using the Rényi entropies.…”
Section: Uncertainty Relation In the Absence Of A Quantum Memorymentioning
confidence: 99%